(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Development and morphogenesis of relictual endemic of Crimean Mountains Silene jailensis (Caryophyllaceae) are studied on the early stages of onthogenesis. The juvenile and immature stages of onthogenesis take one season. In virginal stage, perennial one-axial woody shoot is formed with vegetative apex that functions together with lateral shoots both in lower and terminal parts of the plant. This shoot structure is repeated in the main axle system with branching and forming lateral skeleton shoots.